Nonparametric estimation of the dependence of a spatial point process on spatial covariates - Baddeley, Adrian; Chang, Y.; Song, Y.; Turner, R. (INT PRESS BOSTON, INC, 2012)
In the statistical analysis of spatial point patterns, it is often important to investigate whether the point pattern depends on spatial covariates. This paper describes nonparametric (kernel and local likelihood) methods for estimating the effect of spatial covariates on the point process intensity. Variance estimates and confidence intervals are provided in the case of a Poisson point process. Techniques are demonstrated with simulated examples and with applications to exploration geology and forest ecology.